Role of nubbin in the development of forewing sound-producing structures in Acheta domesticus (house cricket) - Turchyn, Nataliya; Popadić, Aleksandar (Frontiers in Ecology and Evolution, 2024)
Among insects, Orthoptera (crickets and grasshoppers) have evolved a set of highly specialized structures for acoustic communication, with males engaged in sound production and amplification (stridulation) and females in sound reception. These structures in males are located on their forewings, suggesting that some of the wing genes may have been co-opted for new roles in stridulation. As previous studies have identified nubbin (nub) as one of the key genes in the wing development network, we examined its function in the house cricket, Acheta domesticus. Our results show that nub regulates the overall size and venation of both fore- and hindwings in both sexes, consistent with its general role in wing development. Moreover, in males this gene is also involved in the development of sound resonators (primarily the harp, anal area, mirror, and chord). The distinct morphology of these structures is generated by either the activation (in the harp and anal area) or suppression (in the mirror and chord) of vein and cross-connection development in localized regions of the forewings. Finally, nub RNAi males do not stridulate, confirming that the observed changes in the morphology of resonators are functionally significant and responsible for the loss of sound production.